Road Maps of the Transition : The Baltics, the Czech Republic, Hungary, and Russia - Marrese, Michael (Occasional Papers; Occasional Paper, 1995)
Four papers analyze the process of transition to a market economy in the Baltics, the Czech Republic, Hungary, and Russia through early 1995.